Football and Ice Hockey Fans' Experience of a 12-Week Training and Weight-Loss Pilot Intervention (ViSiT) in Sweden—A Focus Group Study - Skagerström, Janna; Hjertstedt, Magdalena; Dannapfel, Petra; Müssener, Ulrika; Leijon, Matti (Frontiers in Sports and Active Living, 2021)
Background: Excess weight is associated with an increased risk of poor health and premature mortality. This is more important for men than for women because men have a lower life expectancy and a higher prevalence of several lifestyle-related diseases. A concept whereby overweight male supporters of professional football clubs are recruited and offered a weight-loss intervention has been developed in Scotland. In the present study, we explore participants’ experiences of a similar intervention, called ViSiT, conducted with supporters in one hockey club and one football club in Sweden. Methods: In this user centred evaluation focus groups were conducted with 12 men who had completed the 12-week ViSiT intervention. Participants discussed reasons for participating in and completing in the intervention, effects of the intervention, advantages and areas of improvement of the intervention, and thoughts on the club’s involvement. The material was analysed using thematic analysis according to Braun and Clarke. Results: The analyses revealed four themes: reasons to participate, motivation and reinforcement, change of habit, and areas for improvement. The intervention was seen as an opportunity to change daily lifestyle behaviours. The group format, as well as the involvement of a prestigious sports club, was important for signing up to the intervention and for motivating continued involvement. The intervention had also increased knowledge on health and had changed mindsets about being more attentive to regulating day-to-day behaviour. Although the overall feedback on the intervention was positive, the participants suggested that possibilities to have more individual coaching should be added. Conclusions: The ViSiT lifestyle intervention may be feasible in a Swedish context to reach overweight men at risk of poor health. The hockey and football club supporters expressed similar experiences from participating in the intervention. ViSiT seem to have a potential to be adopted by many sports clubs for a widespread reach to a group normally considered reluctant to participate in lifestyle change programs.